The Effect of Store Image on Consumers’ Store Brand Purchase Frequency and Perceived Quality of Store Brands around Chennai City - Venkateswaran, N.; Mahalakshmi, V. (Indian Journal of Marketing, 2010)
Store brands, also known as private labels, are main stream in many markets and are becoming more so, particularly in developing markets. As such, they constitute legitimate threats to established brands. As retailers update store brand packaging and roll out premium lines of private labels, shoppers seem increasingly willing to try these products. Positive store image is a key asset for retailers to achieve and sustain success in an increasingly competitive marketplace. Because of this, retailers are trying to make their customers perceive their store image positively. Retailers who manage their image effectively can influence consumers’ store patronage decisions and improve their competitive situation. On the other hand, store brands - that are unique to the store - may increase customer traffic and generate greater store loyalty. Store image is composed of many dimensions and knowing which dimensions of the store image contribute positively to the perceived quality of store brands can provide retailers with a strategic advantage. By investing in those specific dimensions, they can gain the advantage of store image on the one hand and on the other hand, can transfer this positive image to the perceived quality of their store brands, which are generally perceived as low quality compared to the national brands. A store brand can be successful in one category and can be unsuccessful in another category. This may be because of the variances in promotional activities, design of package, and the perceived quality of store brands in different product categories or may be because of the store image. In more developed Asia Pacific markets such as Australia, store brands enjoy a 25% share of sales. Conversely, other countries in the region with limited modern trade offer fewer store brands. Store brands follow Western retailers as they enter a market and local retailers are quick to follow suit with their own store brand lines. Thailand is a great example, where Carrefour recently launched an ad campaign exclusively featuring store brands.